Perancangan Perangkat Keras MPPT Metode Perturb and Observation - Safarudin, Yanuar Mahfudz; Mariani, Dina; Hendrawati, Dwiana; Suwarti, Suwarti; Ali, Machrus; Nurrohmah, Hidayatul (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2018)
This study discusses the use of perturb and observation algorithm in the application of maximum power point tracking. The algorithm is simulated and tested hardware in two shading conditions. The results show the similarity result of hardware testing and simulation.